Measurement of [psi](2S) meson production in pp collisions at √s = 7 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; et al. (The European physical journal. C, Particles and fields, 2012)
The differential cross-section for the inclusive production of ψ(2S) mesons in pp collisions at $\sqrt{s}=7\ \mbox{TeV}$has been measured with the LHCb detector. The data sample corresponds to an integrated luminosity of 36 pb−1. The ψ(2S) mesons are reconstructed in the decay channels ψ(2S)→μ+μ− and ψ(2S)→J/ψπ+π−, with the J/ψ meson decaying into two muons. Results are presented both for promptly produced ψ(2S) mesons and for those originating from b-hadron decays. In the kinematic range pT(ψ(2S))≤16 GeV/c and 2<y(ψ(2S))≤4.5 we measure where the last uncertainty on the prompt cross-section is due to the unknown ψ(2S) polarization. Recent QCD calculations are found to be in good agreement with our measurements. Combining the present result with the LHCb J/ψ measurements we determine the inclusive branching fraction where the last uncertainty is due to the $\mathcal{B}(b \rightarrow J/\psi X)$, $\mathcal{B}(J/\psi\rightarrow\mu^{+} \mu^{-})$and $\mathcal{B}(\psi(2S) \rightarrow e^{+} e^{-})$branching fraction uncertainties.